Hamiltonian fuzzy graphs with application to human trafficking - Ali, Shanookha; Mathew, Sunil; Mordeson, J N (Information sciences, 2021)
•Generalizations of classic results by Bondy and Dirac.•Introduction of Hamilitonicity in fuzzy set up.•Algorithms and Applications. Bottlenecks create delay and traffic jams in interconnection networks. Allowing more paths and cycles of larger capacities can ease this problem to some extent. A path of maximum size is said to be a heavy path. In this paper, some results on heavy paths, heavy cycles and Hamilton cycles are presented. A generalization for Dirac’s theorem in graph theory is discussed in a fuzzy set up. Algorithms for the determination of heavy paths and heavy Hamilton cycles and an application of heavy paths in human trafficking are also proposed.